2017
DOI: 10.1007/s10764-017-9998-1
|View full text |Cite
|
Sign up to set email alerts
|

The Number of Louse Eggs on Wild Japanese Macaques (Macaca fuscata) Varies with Age, but Not with Sex or Season

Abstract: During grooming, primates remove harmful ectoparasites, such as ticks and lice, and there is direct evidence for a health benefit of tick removal. Grooming behaviors differ among primates with respect to age and sex. Moreover, the number of ectoparasite may exhibit seasonal variation. Therefore the number of ectoparasites on a host may vary with effects, host age and sex, and season. However, these effects have not been a focus of louse infestation studies of primates. Grooming in Japanese macaques is related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The female was regularly observed grooming the male while sleeping. Allogrooming in solitary species is typically observed only during the breeding or rearing of young and facilitates courtship, bonding, cleanliness, and social rank (Sachs 1988;Smolinsky et al 2009;Ishii et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The female was regularly observed grooming the male while sleeping. Allogrooming in solitary species is typically observed only during the breeding or rearing of young and facilitates courtship, bonding, cleanliness, and social rank (Sachs 1988;Smolinsky et al 2009;Ishii et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Among the most widely stated host‐related determinants of parasite richness and prevalence are species, sex, age, and body condition (e.g., Clough et al, 2010; Durden et al, 2021; Ishii et al, 2017; Klein et al, 2018). The impact of host species on parasite infections can result from differences in ecology and sociality.…”
Section: Introductionmentioning
confidence: 99%
“…Since older individuals could show immunosenescence (Haberthur et al, 2010; Palacios et al, 2007; Zohdy, 2012), or juveniles could have less developed immune systems (Attanasio et al, 2001; Foerster et al, 1997), age has been argued and shown to impact parasitic infections. In a study on wild Japanese macaques ( Macaca fuscata ), Ishii et al (2017) found that juvenile hosts harbored more louse eggs than adult macaques. As a consequence of nutritional stress, hosts in poorer body conditions are often more susceptible to infections than individuals in better conditions (Beldomenico & Begon, 2010; Kiene et al, 2020; Wikel, 1982).…”
Section: Introductionmentioning
confidence: 99%